Early individual stakeholders, first venture capital investment, and exit in the UK startup ecosystem - Banal-Estañol, Albert; Macho-Stadler, Inés; Nieto-Postigo, Jonás; Pérez-Castrillo, David (Journal of Corporate Finance, 2023)
We create a novel, comprehensive dataset of UK-based startups with extensive information on ownership, control, and valuation. Our database provides unique descriptive evidence about the relevance of individual stakeholders in startups, particularly before the entry of venture capital institutional investors. We compare the influence of two comparable characteristics of various groups of pre-institutional individual stakeholders: size and experience. We show that the quantity as well as the experience, of founders, directors, and other individual investors correlate with the startup’s type of, and value at, exit. Success results are very different across types of diversity: functional diversity appears to have a positive relationship with success whereas that of demographic diversity is negative.